2012
DOI: 10.5194/tc-6-841-2012
|View full text |Cite
|
Sign up to set email alerts
|

Surface and snowdrift sublimation at Princess Elisabeth station, East Antarctica

Abstract: Abstract. In the near-coastal regions of Antarctica, a significant fraction of the snow precipitating onto the surface is removed again through sublimation -either directly from the surface or from drifting snow particles. Meteorological observations from an Automatic Weather Station (AWS) near the Belgian research station Princess Elisabeth in Dronning Maud Land, East-Antarctica, are used to study surface and snowdrift sublimation and to assess their impacts on both the surface mass balance and the surface en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 66 publications
0
43
1
Order By: Relevance
“…Also at PE, most of the blowing snow events (N = 1643, 92 %) are associated with the warm synoptic and transitional regimes, when moist air is brought from the ocean, that precipitate inland (Gorodetskaya et al, 2013). Thiery et al (2012) also showed that at PE drifting snow sublimation occurs mostly during transitional regimes. These regimes occur 41-48 % of the time (Gorodetskaya et al, 2013.…”
Section: Blowing Snow and Meteorological Regimesmentioning
confidence: 90%
See 1 more Smart Citation
“…Also at PE, most of the blowing snow events (N = 1643, 92 %) are associated with the warm synoptic and transitional regimes, when moist air is brought from the ocean, that precipitate inland (Gorodetskaya et al, 2013). Thiery et al (2012) also showed that at PE drifting snow sublimation occurs mostly during transitional regimes. These regimes occur 41-48 % of the time (Gorodetskaya et al, 2013.…”
Section: Blowing Snow and Meteorological Regimesmentioning
confidence: 90%
“…This phenomenon occurs approximatively on 70 % of the Antarctic continent during winter (Palm et al, 2011). In addition, drifting and blowing snow sublimation contributes substantially to SMB (Kodama et al, 1985;Takahashi et al, 1992;Thiery et al, 2012;Dai and Huang, 2014). This process can even be more effective to remove mass than surface sublimation (van den Broeke et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the complete SEB contains turbulent fluxes as well, which can play an important role in energy exchanges between surface and atmosphere (Curry et al, 2000;Van Den Broeke et al, 2006;de Boer et al, 2014) and in mass-related processes such as sublimation (Thiery et al, 2012), in addition to the radiative fluxes considered here. Since turbulent fluxes cannot be retrieved from CloudSat and CALIPSO observations, these are not included in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Both drifting snow sublimation and surface sublimation have been quantified for the PE station (Thiery et al, 2012). At the 5 local scale, their significance can be fairly large (e.g.…”
mentioning
confidence: 99%